Locally Advanced Disease and Pelvic Exenterations - Kontovounisios, Christos; Tekkis, Paris (Clinics in Colon and Rectal Surgery, 2017)
Advanced primary and recurrent colorectal cancer can be successfully treated by experienced, dedicated centers delivering good outcomes with low mortality and morbidity. Development and implementation of a comprehensive referral pathway is to be encouraged. Multidisciplinary team management is essential in the management of this complex group of patients and is associated with significantly more complete preoperative evaluation and more accurate provision of patient information, as well as improved access to the most appropriate individualized management plan. A structured selection process can improve outcomes through standardized approaches to service delivery to provide the highest quality of care.
Keywords: primary advanced rectal cancer; recurrent rectal cancer; beyond total mesorectal excision; multidisciplinary management